Exact solution of the cylindrical Korteweg–de Vries equation for dust ion acoustic wave in unmagnetised plasma. (6th November 2015) - Ghosh, S K; Gupta, S K; Chatterjee, P
Abstract: The cylindrical Korteweg–de Vries equation is derived for dust ion acoustic waves in unmagnetized plasma by employing reductive perturbation technique. Lie group analysis is employed to obtain exact solution of the cylindrical Korteweg–de Vries equation. The original non-planar system is mapped by invertible point transformations to the equivalent autonomous planar form to obtain exact solutions. It is found that the non-planar cylindrical geometry differs from that of the planar one-dimensional geometry.